Laboratory life [ the construction of scientific facts - Latour, Bruno; Woolgar, Steve (Princeton University Press, 1986)
This highly original work presents laboratory science in a deliberately skeptical way: as an anthropological approach to the culture of the scientist. Drawing on recent work in literary criticism, the authors study how the social world of the laboratory produces papers and other "texts,"and how the scientific vision of reality becomes that set of statements considered, for the time being, too expensive to change